(untitled) (Pesquisa Odontológica Brasileira, 2000)
The aim of this work was to evaluate the in vitro compatibility between some composite resins (Herculite XR, Z100 and AP.H) and different adhesives (XR-Bond, Scotchbond MP and PUB3), since for various reasons, the utilization of composite resins and adhesives from different commercial brands is very frequent in the dental practice. We used a device constituted of a base and a matrix which, when juxtaposed, showed a cavity in dumbbell shape which received the composite resin. Firstly, 45 half-specimens of each composite resin were made and stored in distilled water at 37ºC for one week. Then, they were replaced in the matrix for the building of the second half and divided into groups to combine each composite resin with each one of the three adhesives. The specimens were stored in distilled water at 37ºC and after the period of 7 days they were submitted to the tensile strength test in a Kratos machine. It was concluded that: generally, the composite resins and the adhesives showed to be compatible; the combination AP.H/XR-Bond showed the highest discrepancy, since the tensile strength was statistically smaller than that of the combination proposed by the manufacturer; the other combinations of the adhesives and the composite resins showed tensile strengths statistically similar to or greater than that of the combination recommended by the manufacturer.